The Forgotten Ones: Crafting for Meaning and for Affiliation in the Context of Finnish and Japanese Employees' Off-Job Lives - Kujanpää, Miika; Weigelt, Oliver; Shimazu, Akihito; Toyama, Hiroyuki; Kosenkranius, Merly; Kerksieck, Philipp; de Bloom, Jessica (Frontiers in Psychology, 2021)
In an intensifying working life, it is important for employees to proactively shape their lives beyond work to create opportunities for satisfying personal needs. These efforts can be beneficial for creating and sustaining wellbeing in terms of vitality. In this study, we focused on off-job crafting for meaning and off-job crafting for affiliation, conceptualized as proactive changes in off-job life with the aim of increasing satisfaction of needs for meaning and affiliation, among employees in Finland and Japan, two countries with disparate cultural values. We examined longitudinal within-person relationships between the two off-job crafting dimensions and vitality, as well as the relationships between off-job crafting and contextual variables, such as age and gender. We conducted a longitudinal study over six months with three measurement points. A total of 578 Finnish and 228 Japanese employees participated in the study. Hypotheses were tested with Latent Growth Analysis. Increases in off-job crafting for meaning and for affiliation were mostly positively related to increases in vitality over time in both countries. In Finland, age was positively related to off-job crafting for meaning. In Japan, age was negatively related to off-job crafting for meaning and female gender was positively related to off-job crafting for affiliation. Focusing on increasing meaning and affiliation in off-job life can be beneficial strategies for employees to feel positively energized. The role of contextual variables and culture in off-job crafting should be examined further in future studies.